2006
DOI: 10.1016/j.ecss.2006.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the food webs of two intertidal mudflats during two seasons using inverse modelling: Aiguillon Cove and Brouage Mudflat, France

Abstract: Inverse analysis was used to model the food webs of two intertidal mudflat ecosystems: Aiguillon Cove (AC) and Brouage Mudflat (BM) (south-western Atlantic coast, France). The aim of the present study is to describe and compare the functioning of these two ecosystems. The method of inverse analysis has been adapted in order to take into account, in a single calculation, two seasons: spring/summer (mid-March to mid-October) and autumn/winter (the rest of the year). Gathering all available data on the two sites,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 66 publications
5
28
2
Order By: Relevance
“…DEGRÉ et al (2006) found that the grazing fish, which kept a roughly equilibrated diet between microphytobenthos and detritus, changed their exclusively herbivorous diet during summer to prey on nematofauna during winter in a mudflat. This fluidity among guilds exists because ecological interactions among species are intensified at certain periods, with the less competitive species or species more susceptible to predation being excluded or replaced by species with greater adaptability to environmental pressures (ARAÚJO et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…DEGRÉ et al (2006) found that the grazing fish, which kept a roughly equilibrated diet between microphytobenthos and detritus, changed their exclusively herbivorous diet during summer to prey on nematofauna during winter in a mudflat. This fluidity among guilds exists because ecological interactions among species are intensified at certain periods, with the less competitive species or species more susceptible to predation being excluded or replaced by species with greater adaptability to environmental pressures (ARAÚJO et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The Brouage mudflat has become the best-studied mudflat of Marennes-Oléron Bay and an important experimental site due to its exceptional morpho-sedimentological features (Bassoullet et al, 2000) and high primary productivity (Guarini et al, 1997). Most of the components of the Brouage ecosystem have been studied: the abundances and diversity of macrofauna, meiofauna and flora (Cariou-Le Gall and Blanchard, 1995;Rzeznik-Orignac et al, 2003;Sauriau et al, 1989) and numerous data are available on its benthic ecology (Degré et al, 2006;Leguerrier et al, 2003;.…”
Section: Study Sitementioning
confidence: 99%
“…Meiofauna can contribute up to 30% of the living biomass in sediment, and it is assumed that their contribution to the food of deposit-feeding macrofauna is of similar magnitude (Coull, 1990(Coull, , 1999Degré et al, 2006;Gerlach, 1978;Leguerrier et al, 2003). Meiofauna feed on bacteria, diatoms and protozoa as well as other small organisms.…”
Section: Introductionmentioning
confidence: 99%
“…They play a key role in the trophic web of intertidal mudflats (Degré et al, 2006). There are about 4000 benthic species, with hundreds of living individuals being easily found in a few cubic centimetres of sediment (Schö nfeld et al, 2012).…”
Section: Introductionmentioning
confidence: 99%